Towards a digital tool for monitoring and reporting mobile victimisation among South African high school students - Lusinga, Shallen (Department of Information Systems, 2020)
Mobile victimisation is one form of cyber aggression that is increasing and affecting many young people in the developing world today. However, the focus on mobile victimisation in developing nations is limited. There is also limited theoretical work to enhance the conceptualisation of mobile victimisation. Understanding this phenomenon in developing countries is particularly critical as mobile phone usage and crime in these countries are among the highest in the world. Literature shows that in addition to these challenges, schools that have adopted paper or program-based interventions have not been very successful in combating victimisation. Research from other disciplines, however, suggests that digital interventions effectively address health and psychological challenges by offering digital self-intervention. Research shows that reporting bullying incidents is a form of intervention whose challenges in developing and maintaining mechanisms persist. Schools particularly lack systems for reporting and students do not trust some of the reporting mechanisms. Similar problems have been identified in cyberbullying literature. Reporting violence in schools is particularly important in a country like South Africa, where the rate of crime remains the highest in the world. Understanding the circumstances under which victims decide to report (or not report) is important for effective development and implementation of appropriate interventions. Studies on crime reporting provide mechanisms for predicting reporting behaviour that are mainly based on sociological, economic or psychological models. Given that this study investigated reporting behaviour from a technological perspective, technological models were also considered. However, focusing on one theoretical model may fail to capture the complexity of the factors influencing a victim's decision whether or not to report aggression. A broader theoretical perspective would allow for the identification of the various motivating factors which generally do not operate exclusively. In addition, most existing studies have focused on traditional forms of violence. Victimisation in schools is increasingly committed using mobile technology, making it imperative to examine the problem of reporting in a mobile environment. Reporting practices in a digital context may, however, differ in some aspects from reporting in a non-technological environment and these may vary across cultural groupings. Applying a design science research (DSR) process within a pragmatic paradigm and being informed by literature, this study developed an integrative framework for understanding the under-reporting of mobile victimisation by students so as to inform the development of a mobile-based intervention. Findings from the study confirmed that students do not report their victimisation because of economic, psychological, cultural-sociological and technological factors as predicted by the integrative theoretical framework. This confirmed the complexity of the factors influencing students decision whether or not to report aggression. This, therefore, implied that the proposed framework is not only valuable in explaining the broad socialcultural context of victimisation reporting, but also in reporting behaviours at the individual level. The proposed framework, therefore, informed the design, development and evaluation of a mobile application for reporting mobile victimisation faced by high school students in South Africa. An application named the Mobile Victimisation Monitoring and Reporting (MVMR) application was then developed and evaluated among high school students. The MVMR application (app) provides useful features that enable: reflection by students; empathy from adult figures; empowerment for the students; consequence for the bullies. It also mitigates students’ fear and provides them with the ability to control their reporting. Of the features engrained in the MVMR app to capture these themes, students found the option to report anonymously, the option to identify the bully and the display of their frequency of mobile phone use to be the most relevant and useful. The study makes significant contribution to knowledge by providing insights into the reporting behaviours of high school students, which is an understudied research area. One essential theoretical contribution was the development of an integrative theoretical framework that provides the theoretical and social-ecological underpinnings to reporting behaviour which have previously been broad-brush approaches given to a whole class or whole school. Concerning the contribution to practice, the study produced an IT artefact that is based on the proposed integrative theoretical framework. With this tool, high school students will have a means by which to report their victimisation and have the report addressed by an administrator who has a social-ecological understanding of that student. This creates a shift from generalised interventions and creates a more personalised approach to intervening mobile victimisation. Further discussions on the theoretical, practical and methodological contributions are made in this thesis, along with the limitations of the study and recommendations for future research.